1991
DOI: 10.1111/j.1439-0434.1991.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

New Races of the Sunflower Downy Mildew Pathogen (Plasmopara halstedii) in Europe and North and South America

Abstract: Collections of the causal agent of sunflower downy mildew (Plasmopara balstedii) (PH) from several European and North and South American countries were used to inoculate a series of sunflower inbred lines to differentiate races. Race 3 was identified from Argentina; race 4 from France, Hungary, and Bulgaria; race 6 from Canada and France; and race 7 from Argentina. This is the first report of race 3 in South America and of race 4 in Europe, and is the first identification of races 6 and 7. Reactions of USDA li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 6 publications
1
54
0
1
Order By: Relevance
“…In Europe, breeding programmes led to all widely grown varieties carrying the resistance genes Pl1 and Pl2 and there followed almost 20 years (until 1988) with no problem from this disease. However in the USA, problems appeared more quickly, with new races from 1980 (Gulya et al, 1991), which could be considered to be logical co-evolution. Chemical control (by metalaxyl seed treatment) was only of very temporary use, the parasite soon showed resistance (Albourie et al, 1998).…”
Section: Downy Mildewmentioning
confidence: 99%
“…In Europe, breeding programmes led to all widely grown varieties carrying the resistance genes Pl1 and Pl2 and there followed almost 20 years (until 1988) with no problem from this disease. However in the USA, problems appeared more quickly, with new races from 1980 (Gulya et al, 1991), which could be considered to be logical co-evolution. Chemical control (by metalaxyl seed treatment) was only of very temporary use, the parasite soon showed resistance (Albourie et al, 1998).…”
Section: Downy Mildewmentioning
confidence: 99%
“…Recently, several modifications have been made in the third triplet, e.g. at the position of D8 the USDA's line HA-R5 (Gulya et al 1991) has been replaced by INRA's selection QHP-1 (Tourvieille de Labrouhe et al 2000Labrouhe et al , 2012 and newly by a further reselection named QHP-2 (Pierre Desray, INRA, pers. comm.).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of P. halstedii races was confirmed in the 1970s when a new race was detected in the USA which was able to overcome sunflower resistance gene Pl 1 , which ensured resistance to the European race (Zimmer 1974). Changes in virulence of P. halstedii in 1980s led to the introduction of a new nomenclature system based on the reaction of nine sunflower differential lines bearing various Pl resistance genes and race identification by a triplet code (Sackston et al 1990;Gulya et al 1991;Gulya 1995 18 races had been reported from Europe (Virányi et al 2015) and 20 races from America (Gulya 2007). Over the past 7 years this number increased to a total of 24 races in Europe and 36 in America.…”
mentioning
confidence: 99%
“…The first report of Pl 2 was published by Zimmer and Kinman (1972) and Fick and Zimmer (1974), who showed that both HA61 and RHA274 harboured a single dominant gene Pl 2 giving resistance to race 300. Based on the gene for gene hypothesis, Gulya et al (1991), suggested that RHA274 carried not only Pl 2 , giving resistance to race 300 but also Pl 9, giving resistance to race 310. However, they did not study genetic segregation patterns for the two genes.…”
Section: Resultsmentioning
confidence: 99%